2010
DOI: 10.3109/09513590.2010.487593
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac conductive disturbance in patients with polycystic ovary syndrome

Abstract: PCOS is associated with a widening QRS duration, which may contribute to its increased cardiovascular risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Gonadal steroid hormone disorders can affect ECG abnormality, but the effects of PCOS on ECGs are still unclear. The QRS duration was wider in PCOS patients [12]. QTc interval duration is short in PCOS patients [13], which is negative related with testosterone.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Gonadal steroid hormone disorders can affect ECG abnormality, but the effects of PCOS on ECGs are still unclear. The QRS duration was wider in PCOS patients [12]. QTc interval duration is short in PCOS patients [13], which is negative related with testosterone.…”
Section: Introductionmentioning
confidence: 83%
“…Until now, there has been few study on the relationship between ST change and PCOS. There were two main reasons [12][13][14]37]. First, the previous studies compared PCOS patients with healthy control, rather than different types of PCOS patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite profound differences in hormonal and metabolic patterns, the ECG pattern in PCOS is not significantly different from healthy individuals [68]. However, a study has suggested that PCOS is associated with widening the QRS interval [69].…”
Section: Polycystic Ovarian Syndromementioning
confidence: 93%